A normative approach for assessment of accessibility from liveability perspective. Issue 1 (2nd January 2021) - İstillozlu, Elda; Doratlı, Naciye
ABSTRACT: The urban problems faced today and the growing competitive environment call for the re-examination of the liveability of cities. Especially, rising urban sprawl and chaotic urban areas with economic, social and environmental problems, which impinge on the liveability of cities demand critical studies to aid policy formulation and implementation. Although the most exact approach is subject to debate, it is notable that accessibility to urban amenities has a crucial impact on the liveability of cities. Moreover, it is argued that accessibility is a subject of functional place quality which is a dimension of liveability. Therefore, assessing accessibility from a liveability perspective would provide a basis for suggesting planning policies and interventions for improving accessibility of cities. Exploring different methodologies and approaches to accessibility measurements have shown that assessing user perception, a normative approach, is the most appropriate for a new liveability-based methodology. Following from these, liveability, as it relates to place quality, has been defined in conjunction with accessibility and mobility. Afterward, accessibility has been explored through a liveability perspective to determine its indicators and criteria for suggesting a normative methodology to be able to make evaluations of accessibility of cities.